2019
DOI: 10.1016/j.isci.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Werner Syndrome Helicase Is Required for the Survival of Cancer Cells with Microsatellite Instability

Abstract: Summary Werner syndrome protein (WRN) is a RecQ enzyme involved in the maintenance of genome integrity. Germline loss-of-function mutations in WRN led to premature aging and predisposition to cancer. We evaluated synthetic lethal (SL) interactions between WRN and another human RecQ helicase, BLM, with DNA damage response genes in cancer cell lines. We found that WRN was SL with a DNA mismatch repair protein MutL homolog 1, loss of which is associated with high microsatellite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 30 publications
1
76
0
Order By: Relevance
“…This indicates on-target WRN knockdown and efficient transgenic complementation ( Figure 1C). Consistent with previous reports (19)(20)(21)27), the WRNr E84A transgene also successfully rescued the WRN depletion viability phenotype ( Figure 1C). Crucially, both the Walker A mutation K577M and the Walker B mutation E669A abrogated the WRNr transgene-mediated rescue of cell viability upon depletion of endogenous WRN ( Figure 1C).…”
Section: Atp-hydrolysis By Wrn Helicase Is Essential For Viability Ansupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates on-target WRN knockdown and efficient transgenic complementation ( Figure 1C). Consistent with previous reports (19)(20)(21)27), the WRNr E84A transgene also successfully rescued the WRN depletion viability phenotype ( Figure 1C). Crucially, both the Walker A mutation K577M and the Walker B mutation E669A abrogated the WRNr transgene-mediated rescue of cell viability upon depletion of endogenous WRN ( Figure 1C).…”
Section: Atp-hydrolysis By Wrn Helicase Is Essential For Viability Ansupporting
confidence: 92%
“…Previous studies (19)(20)(21)27) demonstrated that WRN depletion causes pervasive DNA damage and the loss of viability selectively in MSI-H but not MSS cell lines. Mutational analyses of WRN suggested that ATP-binding of the helicase domain but not enzymatic activity of the exonuclease domain is critical for the survival of MSI-H cells.…”
Section: Atp-hydrolysis By Wrn Helicase Is Essential For Viability Anmentioning
confidence: 98%
See 1 more Smart Citation
“…We have exploited our XL collection to assess if WRN dependency, which has been recently reported as a new synthetic lethality trait in MSI-H cancers (51)(52)(53)(54), could also apply to MSI-like colorectal tumors. MSI-like CRC models are genetically MSS, but bear intrinsic transcriptional features that resemble MSI-H cancers (55).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many papers describing synthetic lethal interactions of DNA helicases have appeared in the literature suggesting a general theme that helicases respond to replication stress via extended networks with numerous genetic interactions (for examples, see [267][268][269][270]). The recent identification of WRN helicase (mutated in Werner syndrome (WS), see below) as a synthetic lethal gene in microsatellite unstable cancers with defects in DNA MMR genes emphasizes the point [271][272][273][274]. The challenge in functional genomics remains to understand how, and in what context, certain DNA helicases have unique pathway functions.…”
Section: Replication Stressmentioning
confidence: 99%